Histological evaluation of latissimus dorsi muscle subjected to tissue expansion after infiltration with botulinum toxin: an experimental study in rats - Manoel Pereira da Silva; Luis Carlos dos Reis; Élia Cláudia de Souza Almeida; Ana Cristina da Rocha Duque; Adriana Cartafina Perez-Bóscollo; Renata Margarida Etchebehere (Revista Brasileira de Cirurgia Plástica, 2018)
The authors describe histological changes in the latissimus dorsi muscle submitted to expansion after relaxation with botulinum toxin. The possible practical benefits include increased muscle compliance and better accommodation of a prosthesis. The experimental model involved 10 Wistar rats (Rattus norvegicus) of the same age, with average weight of 300 g. Muscle biopsies before and after expansion were performed in normal muscle, in a control group (with expanders alone), and in a group with expanders and botulinum toxin. Expanders measuring 3 cm3 were positioned below the muscle and expanded with 0.3 ml of saline weekly, for 10 weeks. Histological sections were stained using hematoxylin-eosin for general evaluation and Masson's trichrome for evaluation of connective tissue. The muscle fibers submitted to expansion under the action of botulinum toxin showed less fibrosis and less intense proliferation of blood vessels than in the group without botulinum toxin, and the atrophy and reduction in the number of muscle fibers were less prominent than in the group that did not receive botulinum toxin. The findings suggest that muscle expansion associated with botulinum toxin relaxation preserves skeletal muscle characteristics by providing better accommodation and protection for a prosthesis and facilitating expansion dynamics; this method may also reduce pain.